The Effect of Adjunctive Questions and Their Position (Pre/Post) in Instructional Materials (Video Tape) on Learning and Retention of Undergraduate Science Students: An Experimental Study - Omar M. Madani Zakari (Journal of Islamic Studies, 2003)
This study was designed to ascertain the effects of using adjunctive questions in instructional media on learning and retention of undergraduate science students. Two hypotheses were generated : 1) The use of adjunctive questions in instructional media facilitates learning and retention: 2) If two groups are differentially exposed to either pre-adjunctive questions or post-adjunctive questions, the group with pre-adjunctive questions will show a greater increase in learning and retention than the group receiving post-adjunctive questions To test these hypotheses an experiment was conducted One hundred and fifty freshmen science students in jazan Teachers College were randomly assigned to three groups · 1) Group 1, pre-adjunctive questions, 2) Group 2, post-adjunctive questions, 3) Group 3, which served as a control group and used no questions at all. Two one-way analysis of variance was selected to test the hypotheses using the post test and the retention test scores There was conclusive evidence in support of the two hypotheses. Students with pre-adjunctive questions (Group 1) preformed significantly higher than both students with post-adjunctive questions (Group 2) and students with no questions at all (Group 3). Students with post-adjunctive questions (Group 2) performed significantly higher then students with no questions at all (i.e., Group 3) on a post test given at the end of instruction and on a retention test given a week later . It was concluded that pre-adjunctive questions should be included in models of instructional design of instructional media, especially video tapes .